2011
DOI: 10.1111/j.1365-2982.2011.01806.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neuromuscular transmission in the W/Wv mouse internal anal sphincter

Abstract: Background Intramuscular interstitial cells of Cajal (ICC-IM) have been shown to participate in nitrergic neuromuscular transmission (NMT) in various regions of the gastrointestinal (GI) tract but their role in the internal anal sphincter (IAS) is still uncertain. Contractile studies of the IAS in the W/Wv mouse (a model in which ICC-IM numbers are markedly reduced) have reported that nitrergic NMT persists and that ICC-IM are not required. However, neither the changes in electrical events underlying NMT nor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(78 citation statements)
references
References 49 publications
6
71
1
Order By: Relevance
“…The fast component of the IJP is inhibited after incubating the tissue with P2Y 1 antagonists such as MRS2179, MRS2279 or MRS2500, suggesting that P2Y 1 receptors are responsible for this mechanism. This pharmacological effect has been demonstrated in several areas of the gastrointestinal tract such as the small intestine (Gallego et al 2008 b ), colon (Gallego et al 2006, 2011; Grasa et al 2009; Zhang et al 2010 b ) and internal anal sphincter (Opazo et al 2011; Duffy et al 2012). All these results suggest that P2Y 1 receptors are responsible for purinergic neurotransmission in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 96%
“…The fast component of the IJP is inhibited after incubating the tissue with P2Y 1 antagonists such as MRS2179, MRS2279 or MRS2500, suggesting that P2Y 1 receptors are responsible for this mechanism. This pharmacological effect has been demonstrated in several areas of the gastrointestinal tract such as the small intestine (Gallego et al 2008 b ), colon (Gallego et al 2006, 2011; Grasa et al 2009; Zhang et al 2010 b ) and internal anal sphincter (Opazo et al 2011; Duffy et al 2012). All these results suggest that P2Y 1 receptors are responsible for purinergic neurotransmission in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 96%
“…The second component is blocked by inhibitors of nitric oxide synthase (NOS) and is therefore regarded as nitrergic (5,23,31). This characteristic biphasic IJP has been shown for several other regions of the GI tract of different species as well, such as antrum (15), small intestine (12), and internal anal sphincter (6,30).…”
mentioning
confidence: 92%
“…however, there is still controversy regarding the role of iCCs in nitrergic transmission in the ias, and some authors have suggested that these cells are part of the nitrergic pathway in murine ias. 16 it is important to consider that the inhibitory neuromuscular transmission in the murine ias involves nitrergic and purinergic components, and, therefore, differences between species could be responsible for conflicting data. 15 the role of the iCC in the rectoanal inhibitory reflex (RaiR) is also unclear.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 so far, the function of iCCs in the ias has only been investigated in 2 using transgenic mice. [13][14][15][16] hypotensive ias has been described in transgenic W/W v mice lacking muscular iCCs, and no clear relationship has been described between iCCs and nitrergic transmission. the role of iCCs in human ias is, therefore, still unclear.…”
mentioning
confidence: 99%